Factors affecting the implementation of labor safety and hygiene in specific enterprises: a case in Vietnam - Kien Vu Gia; Tram Nguyen Thi Huyen; Tuan Le Anh; Hieu Nguyen Trung; Thu Nguyen Lam Kim; Kien Cao Phuoc (Cogent Social Sciences, 2024)
The main content of the article refers to the consideration of factors and their influence on the implementation of occupational safety and hygiene (OSH) risk assessment at enterprises operating in fields with high risks of occupational safety and hygiene in Vietnam. Although the Law on Occupational Safety and Hygiene in Vietnam has been in effect for 5 years, both employees and employers have not yet fully and effectively applied contents related to workplace safety and hygiene. In addition, some guiding contents of this work gradually reveal certain limitations. Based on the guidance on OSH risk assessment currently being applied in Vietnam, combined with standards related to corporate social responsibility (CSR) according to ISO 26000, ISO 45001. The author has developed a questionnaire to survey employers at 230 enterprises operating in industries and occupations with high risks of labor accidents and occupational diseases according to regulations. The results show that there are four factors that affect the implementation of OSH risk assessment in the following order: (1) the ability of business managers, (2) the sense of responsibility of employees and their representatives, (3) labor safety training and (4) legal regulations and safety instructions. In addition, there are many opinions on further improving regulations and OSH risk assessment processes. Based on the results of this research, we would like to make some recommendations to improve the legal system related to the OSH risk assessment process and CSR, and help relevant parties better understand the benefits and raise their awareness of the issue.